The gender dimension in development - Carvajal-Burbano, Arizaldo (Prospectiva. Revista de Trabajo Social e Intervención Social, 2003)
The article addresses development from a gender perspective. It presents four basic dimensions: a conceptualization about gender and its relation to development; the role of women in development, the practical and strategic needs, and the empowerment of women as development actors. Working this perspective implies a greater ethical and political positioning.